The assessment of two-way relationship between periodontal diseases and diabetes mellitus. - Cicalău Georgiana Ioana Potra; Babeș Petru Aurel; Domocoș Daniela; Pogan Mihaela ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2021)
Periodontal disease and diabetes mellitus have been said to have a two-way relationship, with diabetes leading to oral disease and periodontitis exacerbating hyperglycemia. The universal biologic mechanisms and demographic and behavioral risk drivers, underlying these associations in both directions, are also described.